Desenvolvimento de métodos analíticos baseados no princípio de frasco único empregando entalpimetria no infravermelho para controle de qualidade de alimentos e produtos farmacêuticos - Dalla Nora, Flávia Michelon (2018)
The classical methods of chemical quality control such as determination of content uniformity (CU) in medicines, saponification value (SV) in edible oils and active chlorine content in bleaching are often based on volumetric methods. In general, these methods require high amount of sample, too much time for performing the procedure and several steps for execution. In this way, alternative methods of analysis that overcome these disadvantages are interesting for application in laboratory routines. An alternative for the development of more environmentally correct analytical methods is miniaturization, which enables analysis with a minimal waste generation. The integration of analytical processes avoid the use of several flasks, all steps being done in a single reaction flask, minimizing the systematic and random errors, impacting in the quality of the results. In this sense, the thermal infrared enthalpimetry (TIE) technique was used to determine the saponification value in edible oils, the uniformity content in captopril tablets and active chlorine in sodium hypochlorite solutions. For this, microplates and a multichannel pipette were used for the addition of the reagents and an infrared camera for temperature monitoring generated from the chemical reactions were used. In the proposed methods, all operations were performed in microplates, reducing the volume of sample used and performing all analytical steps in the same well. The results obtained by TIE showed suitable accuracy and good agreement with official methods. In addition, it was observed that the proposed methods provided reduction of analysis time and reagent, sample and energy consumption, being a suitable alternative for application in routine analysis, according to the principles of the green analytical chemistry.